We the people : - Ginsberg, Benjamin (W.W. Norton, 2005)
We the People is widely recognized as the classroom standard for introductory American government courses. Maintaining a central emphasis on the relevance of American government and politics to students and continuing to highlight the importance of political participation, the Fifth Edition has been meticulously revised and updated through the 2004 presidential elections, including in-depth analysis of the Iraq War and the "War on Terrorism."